Language dominance, handedness and sex: recessive X-linkage theory and test. - Jones, G; Martin, M (2010)
The possibility is investigated that cerebral dominance for language and handedness share a common X-linkage and that the relation between the two is therefore a function of sex. In particular, an X-linked recessive account is shown to predict an overall configuration of language dominance, handedness and sex within which there is a sex effect in the pattern of language dominance among right-handed but not left-handed people. The recent accurate determination of cerebral dominance among relatively large samples of the general population by means of functional transcranial Doppler ultrasonography makes it possible to test this new theory rigorously, and its parameter-free pattern of predictions is found to be supported.